THE CURRENT STRATEGIES, RECENT PROGRESS AND REMAINING CHALLENGES FOR DEVELOPING MRNA VIRAL VACCINE - Irawan, Priscilla Felicia Apriliani; Bela, Budiman (BRIN - Badan Riset dan Inovasi Nasional, 2024)
The mRNA expression system has revolutionised biotechnology, notably in viral mRNA vaccine development, cancer immunotherapy, and gene therapy. However, recent safety concerns regarding the COVID-19 mRNA vaccine have emerged, particularly regarding its rare adverse effects and its possible connection to cancer. This review explains several approaches used in developing viral mRNA vaccines, the past obstacles solved in generating the current COVID-19 mRNA vaccine, and finally the current advancements and ongoing challenges in the viral mRNA vaccine field. We particularly focus on strategies and methods to improve the safety and translation efficiency of the mRNA vaccine, such as enhancing the vaccine’s transfection specificity to targeted dendritic cells (DC) and using viral IRES or self-amplifying mRNA format to improve mRNA translation efficiency.